2022
DOI: 10.1186/s13287-022-03089-3
|View full text |Cite
|
Sign up to set email alerts
|

PFKFB3-mediated glycometabolism reprogramming modulates endothelial differentiation and angiogenic capacity of placenta-derived mesenchymal stem cells

Abstract: Background Mesenchymal stem cells (MSCs) have a great potential ability for endothelial differentiation, contributing to an effective means of therapeutic angiogenesis. Placenta-derived mesenchymal stem cells (PMSCs) have gradually attracted attention, while the endothelial differentiation has not been fully evaluated in PMSCs. Metabolism homeostasis plays an important role in stem cell differentiation, but less is known about the glycometabolic reprogramming during the PMSCs endothelial differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 91 publications
(114 reference statements)
1
1
0
Order By: Relevance
“…166 In addition, PFKFB3 drives glycolysis, which not only regulates endothelial cell proliferation, migration, and tube formation, but also regulates endothelial differentiation and angiogenic capacity of placenta-derived mesenchymal stem cells (MSCs). 167,168 The aforementioned studies demonstrated the importance of glycolysis in preeclampsia pathogenesis and corroborated the hypothesis that the dysregulation of glycolysis leads to preeclampsia.…”
Section: Preeclampsiasupporting
confidence: 68%
“…166 In addition, PFKFB3 drives glycolysis, which not only regulates endothelial cell proliferation, migration, and tube formation, but also regulates endothelial differentiation and angiogenic capacity of placenta-derived mesenchymal stem cells (MSCs). 167,168 The aforementioned studies demonstrated the importance of glycolysis in preeclampsia pathogenesis and corroborated the hypothesis that the dysregulation of glycolysis leads to preeclampsia.…”
Section: Preeclampsiasupporting
confidence: 68%
“…Moreover, some closely related reproduction pathways were annotated, such as the PI3K-Akt, MAPK, Rap1, mTOR, WNT, and calcium signaling pathways, circadian rhythm, oocyte meiosis, and fructose and mannose metabolism. Astoundingly, ALDOB [ 46 ] and PFKFB3 [ 47 , 48 ] are involved in the fructose and mannose metabolism pathways, which may provide energy for early embryonic development. This means that the prolific goats require more metabolites to maintain high fecundity.…”
Section: Discussionmentioning
confidence: 99%